(untitled) (Jurnal Bahasa, 2018)
This study aims to identify and discuss the use of Malay dialectal words in the novel, Seorang Tua di Kaki Gunung, by Azizi Haji Abdullah. The types of dialectal words in the source text are determined based on the general definition of dialect by Collins (1989) and the detailed classification of dialectal words by Asmah Haji Omar (2008), Mohammed Azlan Mis and Idris Aman (2014) and Kamus Dewan Edisi Keempat (2015). The findings show that there are 68 Malay dialectal words in the source text, of which 53 are in the category of geographical dialect (Kedah or Northern, Kelantan, Terengganu, Pahang and Negeri Sembilan dialects) while the remaining 15 are in the category of social dialect (archaic words, colloquial words and words from classical literature). The apparent use of the Kedah or Northern dialect besides other social dialects is closely related to the time, place and social settings of the novel as well as the author’s own background. Keywords: novel, literature, Azizi Haji Abdullah, Malay dialect